Enhanced enterovirus 71 virus‐like particle yield from a new baculovirus design. Issue 10 (30th June 2015) - Lin, Shih‐Yeh; Yeh, Chia‐Tsui; Li, Wan‐Hua; Yu, Cheng‐Ping; Lin, Wen‐Chin; Yang, Jyh‐Yuan; Wu, Hsueh‐Ling; Hu, Yu‐Chen
ABSTRACT Enterovirus 71 (EV71) is responsible for the outbreaks of hand‐foot‐and‐mouth disease in the Asia‐Pacific region. To produce the virus‐like particle (VLP) vaccine, we previously constructed recombinant baculoviruses to co‐express EV71 P1 polypeptide and 3CD protease using the Bac‐to‐Bac® vector system. The recombinant baculoviruses resulted in P1 cleavage by 3CD and subsequent VLP assembly in infected insect cells, but caused either low VLP yield or excessive VLP degradation. To tackle the problems, here we explored various expression cassette designs and flashBAC GOLD™ vector system which was deficient in v‐cath and chiA genes. We found that the recombinant baculovirus constructed using the flashBAC GOLD™ system was insufficient to improve the EV71 VLP yield. Nonetheless, BacF‐P1‐C3CD, a recombinant baculovirus constructed using the flashBAC GOLDTM system to express P1 under the polh promoter and 3CD under the CMV promoter, dramatically improved the VLP yield while alleviating the VLP degradation. Infection of High FiveTM cells with BacF‐P1‐C3CD enhanced the total and extracellular VLP yield to ≈268 and ≈171 mg/L, respectively, which enabled the release of abundant VLP into the supernatant and simplified the downstream purification. Intramuscular immunization of mice with 5 μg purified VLP induced cross‐protective humoral responses and conferred protection against lethal virus challenge. Given the significantly improved extracellular VLP yield (≈171 mg/L) and the potent immunogenicity conferred by 5 μg VLP, one liter High FiveTM culture produced ≈12, 000 doses of purified vaccine, thus rendering the EV71 VLP vaccine economically viable and able to compete with inactivated virus vaccines. Biotechnol. Bioeng. 2015;112: 2005–2015. © 2015 Wiley Periodicals, Inc.